Challenges in using the internet to evaluate value in orthopaedic surgery. Issue 1 (January 2018) - Bernstein, David N.; Mesfin, Addisu; Bozic, Kevin J.
Abstract : Background: The Internet is one tool commonly used by patients to seek out healthcare information, including for orthopaedics. Our goal was to determine and compare the availability ("findability") of cost, quality, and patient experience information related to orthopaedic services with and without a geographic identifier. Methods: A list of 21 common search terms was compiled a priori. Using Google, each term was searched with and without a geographic identifier; the top 15 results were recorded. Findability, source of information, website ownership, information available (cost, quality, and/or patient experience), and frequency of website updates were noted. Bivariate analysis was used to compare results. Results: The prevalence of provider websites was significantly higher using the geographic identifier (47% vs. 0%, P =0.023). There was a significantly higher prevalence of patient experience information when using the location-specific search terms (59% vs. 11%, 0.036). However, there was no difference in the prevalence of sites offering cost (0% vs. 0%, P =0.99) or quality (59% vs. 33%, P =0.41) information between the two groups. No website in either search provided cost information. Ownership did not differ between the two search groups: government (0% vs. 11%, P =0.35); non-profit (41% vs. 11%, P =0.19); and for-profit (59% vs. 78%, P =0.42). Conclusions: The Internet can be a rich source of quality and patient experience information for orthopaedic patients. However, the use of search engine optimization and other marketing techniques may limit the ability of patients to receive unbiased and complete information.